La tentation du mal. À propos d’Un roi sans divertissement de Jean Giono - Jarosz, Krzysztof (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In 1946, only a year after the World War II, Jean Giono, who became famous inthe years 1929-1939 as a writer describing the human’s struggle with nature, writes A KingAlone (Un roi sans divertissement), a novel which surprises his past readers with one of thecharacters being a serial killer fulfilling the uncontrolled need for entertainment by killingpeople. Langlois, the gendarmerie captain tasked with finding the murderer, attempts tounderstand the motive of the criminal turned from a respected and exemplary citizen intoa potential assassin. Not to become the felon’s imitator, Langlois commits suicide. Giono’snovel is a tale of evil inextricably linked to human nature (the murderer’s name is MonsieurV. like in “voisin” – neighbor). The novel did not gain the popularity it deserved becauseafter the World War II evil was the most willingly looked for in the defeated countries ofthe Axis (Germany, Italy, Japan), and the communist-opposed author was blacklisted byNational Writers’ Committee, controlled by the Stalinists. A King Alone is a personal reflectionof a writer marked by war, constituting the expression of his most pessimistic visionof human nature influenced by Machiavelli, Hobbes and Sade. The message of the novel isambiguous: on the one hand, Langlois prefers committing suicide over being a tool of evilresiding in every person; on the other hand, he interiorizes Mr. V.’s motives by exploringthem, thus becoming – like any other human in Giono’s view – a potential killer. Langlois’last act, when he takes his own life, makes him a figure of dark Christ, permeated by evil,who sacrifices himself not to become another link in the chain of malevolent individualspassing on to the potential imitators the penchant for killing, understood here as the highestform of entertainment and the contemplation of human mortality, embodied by thevictim.